Control of Unexpected Mucor lusitanicus in Litchi Fruit by Hydrocooling with Hypochlorous Acid and Cold Storage - I-Fang Liu; Huey-Ling Lin; Chang-Lin Chen (Horticulturae)
Litchi fruit (Litchi chinensis Sonn.) is highly perishable because its shelf life is significantly limited by pericarp browning and microbial spoilage. While sulfur dioxide (SO2) fumigation has been traditionally used to preserve color and reduce spoilage, concerns over potential health risks have prompted the exploration of safer alternatives. This study investigated the application of hypochlorous acid (HClO) as an alternative treatment during postharvest processes to mitigate pathological decay, targeting Mucor lusitanicus, a fungus primarily responsible for litchi fruit rot in Taiwan. In vitro experiments demonstrated that M. lusitanicus growth was completely inhibited by HClO concentrations at 40 mg L−1 or higher, as well as by temperatures below 1 °C. In vivo experiments further revealed that disease symptoms in inoculated litchi fruit were fully suppressed at 25 °C for seven days after hydrocooling with HClO. When 40 mg L−1 HClO treatment was combined with hydrocooling and subsequent storage at 5 °C, the decay ratio of litchi fruit was reduced to below 3% after 21-day storage. The browning index and disease incidence of litchi fruit hydrocooled with an 8 h hydrocooling delay were significantly lower than those with a 12 h hydrocooling delay after 21 days at 5 °C, followed by 1 day at 26 °C. Therefore, hydrocooling within 8 h of harvest is recommended for commercial scales. This treatment effectively prevented pericarp browning and maintained total soluble solid levels, ensuring the quality. These findings suggest that integrating HClO with hydrocooling not only decreases spoilage and delays pericarp browning but also offers a viable alternative to traditional SO2 fumigation, optimizing the postharvest process and enhancing food safety. This approach can extend the storage ability of litchi fruit while maintaining its quality, providing a safer method for local and international markets.